Todo esto es ficción: base de datos sobre literatura infantil y juvenil digital (2020)
The present research is a study of the digital children's and young adults' literature (LIJD, for its Spanish acronym) that was carried out using digital humanities methodologies. Its purpose is to provide visibility to the creation and research of the LIJD in Hispanic American countries. Moreover, it reviews and documents the creation of the TEEF database, a digital resource where researchers and interested parties can find references concerning digital literature for children and young people, such as works, organizations, stimuli, and tools.